Understanding visual consciousness in autism spectrum disorders - Yatziv, Tal; Jacobson, Hilla (Frontiers in Human Neuroscience, 2015)
The paper focuses on the question of what the (visual) perceptual differences are between individuals with autism spectrum disorders and typically developing individuals. We argue against the view that autistic subjects have a deficiency in the most basic form of perceptual consciousness – namely, phenomenal consciousness. Instead, we maintain, the perceptual atypicality of individuals with autism is of a more conceptual and cognitive sort – their perceptual experiences share crucial aspects with typically developing individuals. Our starting point is Ben Shalom’s (2005, 2009) three-level processing framework for explaining atypicality in several domains of processing among autistics, which we compare with two other tripartite models of perception – Jackendoff’s (1987) and Prinz' (2000, 2005a, 2007) Intermediate Level Hypothesis and Lamme's (2004, 2006, 2010) neural account of consciousness. According to these models, whereas the second level of processing is concerned with viewer-centered visual representations of basic visual properties and incorporates some early forms of integration, the third level is more cognitive and conceptual. We argue that the data suggest that the atypicality in autism is restricted mainly to the third level. More specifically, second-level integration, which is the mark of phenomenal consciousness, is typical, yet third-level integration of perceptual objects and concepts is atypical. Thus, the basic experiences of individuals with autism are likely to be similar to typical subjects’ experiences; the main difference lies in the sort of cognitive access the subjects have to their experiences. We conclude by discussing implications of the suggested analysis of experience in autism for conceptions of phenomenal consciousness.